Flow Boiling in Rectangular Microchannels: 1-D Modeling of the Influence of Inlet Resistance on Flow Reversal. Issue 13 (21st September 2016) - Gedupudi, Sateesh; Kenning, David B. R.; Karayiannis, Tassos G.
Abstract : Pressure changes caused by the growth of confined bubbles during flow boiling in mini-/microchannels lead to transient flow reversal in the presence of inlet (upstream) compressibility. A one-dimensional (1-D) model is presented to study the effect of inlet resistance on maximum flow reversal distance, local pressure fluctuations for different initial upstream compressible volumes, channel dimension, locations of nucleation site, heat flux, and initial channel velocity for water and FC-72 at atmospheric pressure and R134a at 800 kPa. The two upstream compressibility models considered are condensable vapor in a subcooled boiling region and trapped noncondensable gas.